TikTok-Driven Buying Patterns: A Study of Consumer Behavior among University Students in the Philippines - Narsico, Peter G.; Jayma, Jozette Sheen A.; Narsico, Lalaine O.; Codilla, Fiona Mae B.; Solon, Rhoda Mae E. (Future Science / FSH-PH Publications, 2025)
TikTok has transformed Generation Z’s consumer behavior through algorithm-driven content, viral trends, and influencer impact. This study examined TikTok’s influence on 345 university students in Cebu City, assessing exposure (time spent, frequency, user-generated content influence, engagement) and consumer behavior (purchase frequency, intention, brand loyalty, impulse buying). Due to significant non-normality confirmed by Shapiro-Wilk tests, Spearman’s rho was used to analyze relationships. Results revealed a significant positive correlation between TikTok exposure and buying behavior (ρ = 0.480, p < .001), with user-generated content exerting the strongest effect (ρ = 0.517). Impulse buying was notably influenced (ρ = 0.458), especially in fashion and personal care. Findings suggest marketers should leverage authentic peer content and influencer partnerships to engage Gen Z and build brand loyalty, while educators should promote digital literacy to help students critically assess content and control impulse purchases. TikTok serves as both an entertainment platform and a powerful marketing tool, highlighting the need for ethical marketing and informed consumer awareness.